2009
DOI: 10.1007/s10661-008-0613-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying structural physical habitat attributes using LIDAR and hyperspectral imagery

Abstract: Structural physical habitat attributes include indices of stream size, channel gradient, substrate size, habitat complexity, and riparian vegetation cover and structure. The Environmental Monitoring and Assessment Program (EMAP) is designed to assess the status and trends of ecological resources at different scales. High-resolution remote sensing provides unique capabilities in detecting a variety of features and indicators of environmental health and condition. LIDAR is an airborne scanning laser system that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
2
35
0
2
Order By: Relevance
“…Previous studies also show the potential of LiDAR data to describe riparian vegetation; but most of these are focused on forest applications (Farid et al, 2006(Farid et al, , 2008Greenberg et al, 2012;Wasser et al, 2013). Only a few studies can be found on the potential of LiDAR data to describe the ecological attributes of riparian zone (Hall et al, 2009;Johansen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also show the potential of LiDAR data to describe riparian vegetation; but most of these are focused on forest applications (Farid et al, 2006(Farid et al, , 2008Greenberg et al, 2012;Wasser et al, 2013). Only a few studies can be found on the potential of LiDAR data to describe the ecological attributes of riparian zone (Hall et al, 2009;Johansen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, remote sensing has enabled synoptic views of entire rivers and their catchments at increasingly fine resolutions. It can now provide data at resolutions that capture reach-scale riparian and instream habitat structuring (Hall et al 2009). …”
Section: Methods and Data In Land Use Analysismentioning
confidence: 99%
“…Recent successes in manned-aircraft RS of riverine environments demonstrates spatial and spectral resolutions that may meet accuracy requirements for measuring many rPHA variables, thus suggesting that similar results can be achieved with drone-based RS [33]. While drone-based spatial and spectral technologies can supply many rPHA quantitative data, determining the most appropriate drone-based sensor(s) to enhance the development of rPHA requires further research.…”
Section: Challenges Using Geographic Information Systems and Remote Smentioning
confidence: 99%
“…Contemporary GIS/RS approaches are being developed to scale down from the watershed or basin level to the stream reach, including in some cases, characterization of channel morphology and other physical habitat attributes [32,33]. For example, Reference [33] demonstrated the integration of airborne Light Detecting and Ranging (LiDAR) technology and hyperspectral imagery to produce high spatial resolution geospatial data of topography, channel dimensions/complexity (e.g., width, depth, slope, riffles/pool spacing), hydraulic roughness, riparian integrity, and anthropogenic alterations.…”
Section: Challenges Using Geographic Information Systems and Remote Smentioning
confidence: 99%
See 1 more Smart Citation